Oxygen-charged HTK-F6H8 emulsion reduces ischemia-reperfusion injury in kidneys from brain-dead pigs. - Asif, S; Sedigh, A; Nordström, J; Brandhorst, H; Jorns, C; Lorant, T; Larsson, E; Magnusson, P; Nowak, G; Theisinger, S; Hoeger, S; Wennberg, L; et al. (2012)
BACKGROUND: Prolonged cold ischemia is frequently associated with a greater risk of delayed graft function and enhanced graft failure. We hypothesized that media, combining a high oxygen-dissolving capacity with specific qualities of organ preservation solutions, would be more efficient in reducing immediate ischemia-reperfusion injury from organs stored long term compared with standard preservation media. METHODS: Kidneys retrieved from brain-dead pigs were flushed using either cold histidine-tryptophan-ketoglutarate (HTK) or oxygen-precharged emulsion composed of 75% HTK and 25% perfluorohexyloctane. After 18 h of cold ischemia the kidneys were transplanted into allogeneic recipients and assessed for adenosine triphosphate content, morphology, and expression of genes related to hypoxia, environmental stress, inflammation, and apoptosis. RESULTS: Compared with HTK-flushed kidneys, organs preserved using oxygen-precharged HTK-perfluorohexyloctane emulsion had increased elevated adenosine triphosphate content and a significantly lower gene expression of hypoxia inducible factor-1α, vascular endothelial growth factor, interleukin-1α, tumor necrosis factor-α, interferon-α, JNK-1, p38, cytochrome-c, Bax, caspase-8, and caspase-3 at all time points assessed. In contrast, the mRNA expression of Bcl-2 was significantly increased. CONCLUSIONS: The present study has demonstrated that in brain-dead pigs the perfusion of kidneys with oxygen-precharged HTK-perfluorohexyloctane emulsion results in significantly reduced inflammation, hypoxic injury, and apoptosis and cellular integrity and energy content are well maintained. Histologic examination revealed less tubular, vascular, and glomerular changes in the emulsion-perfused tissue compared with the HTK-perfused counterparts. The concept of perfusing organs with oxygen-precharged emulsion based on organ preservation media represents an efficient alternative for improved organ preservation.